The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.scs.2017.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Numerical evaluation of thermal comfort in traditional courtyards to develop new microclimate design in a hot and dry climate

Abstract: The growing interest in thermal comfort of outdoor environments yields in different analysis on courtyards as a common space between urban and architectural scales. However, there is a limited knowledge regarding the microclimatic behavior of such spaces. Using ENVI-met simulations, this paper aims to numerically discuss the thermal performance of different configurations of traditionally designed courtyards in Shiraz, Iran, which experiences hot summers and cold winters. The geometrical effects such as orient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(45 citation statements)
references
References 74 publications
2
35
0
Order By: Relevance
“…Previous research optimized design of opening level of courtyards by CFD (Computational Fluid Dynamics) simulation and experimental measurement to improve natural ventilation performance in hot summer and cold winter (HSCW) climate zones ( Hao et al, 2019 ). To improve natural ventilation and thermal comfort in courtyards, courtyard layout, aspect ratio, height-width ratio and southward orientation were optimized by numerical simulations ( Nasrollahi, Hatami, Khastar, & Taleghani, 2017 ; Xu, Luo, Wang, Hong, & Fu, 2018 ). Similarly, the influences of opening angles/distributions, incoming wind orientations and courtyard height on ventilation performance and comfort level were also simulated by using CFD method ( Micallef, Buhagiar, & Borg, 2016 ; Mousa, Lang, & Auer, 2017 ; Subhashini & Thirumaran, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research optimized design of opening level of courtyards by CFD (Computational Fluid Dynamics) simulation and experimental measurement to improve natural ventilation performance in hot summer and cold winter (HSCW) climate zones ( Hao et al, 2019 ). To improve natural ventilation and thermal comfort in courtyards, courtyard layout, aspect ratio, height-width ratio and southward orientation were optimized by numerical simulations ( Nasrollahi, Hatami, Khastar, & Taleghani, 2017 ; Xu, Luo, Wang, Hong, & Fu, 2018 ). Similarly, the influences of opening angles/distributions, incoming wind orientations and courtyard height on ventilation performance and comfort level were also simulated by using CFD method ( Micallef, Buhagiar, & Borg, 2016 ; Mousa, Lang, & Auer, 2017 ; Subhashini & Thirumaran, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Greenery is one of the most effective elements of a human-biometeorological oriented design which plays an important role in improving thermal comfort (Middel et al, 2015, Taleghani and Berardi, 2018, Lee and Mayer, 2018. There are many studies that showed the heat mitigation impacts of vegetation in traditional courtyards (Foruzanmehr and Vellinga, 2011, Nasrollahi et al, 2017, and in urban scale (Akbari andKolokotsa, 2016, Yan et al, 2018) in arid climates. Due to the water shortage in such climates, urban greenery needs to be designed in the most efficient way.…”
Section: Introductionmentioning
confidence: 99%
“…Courtyards tend to be the primary outdoor spaces for recreational activities as well. As a result, landscape architects focus on improving thermal comfort within courtyards during hot summers and cold winters [13,14]. Courtyards with a southward orientation and configurations of high Height/Width can achieve a better thermal comfort level both by shading during summer and regulating the wind speed in winter [14,15].…”
Section: Introductionmentioning
confidence: 99%